Climate, intermittent humidification, and humidifier fever. Issue 9 (September 1989) - Anderson, K; Watt, A D; Sinclair, D; Lewis, C; McSharry, C P; Boyd, G
Abstract : Two summer outbreaks of humidifier fever (HF) are described in a microprocessor factory (factory A) and a printing factory (factory B). The air in each factory was humidified intermittently and controlled by present humidistats operating to maintain a relative humidity of 45% by an air handler incorporating a spray humidifier in factory A and two ceiling mounted spray humidifiers in factory B. Questionnaire data from each workforce suggested that although symptoms apparently occurred most commonly in both factories on return from holiday (41/57, 71.9%), many subjects (24/40, 60%) in factory A also had intermittent symptoms of ill defined periodicity for some time before the disorder was recognised. Similar intermittent symptoms with no discernible pattern occurred in factory B in a smaller number of subjects (4/17, 23.5%), all of whom were night or rotating shift workers. Both episodes of humidifier fever after return from summer holiday developed when nocturnal air temperatures were unseasonably low; not on the day of return to work but two days later (factory A) and one day later (factory B). Symptoms were most common in most workers who had circulating serum IgG antibody measured by ELISA to humidifier sludge in factory B (14/17, 82.9%) but were most common in IgG antibody negative subjects in factory A (27/40, 67.5%). A more classic form of humidifier fever redeveloped in factory B during winter when meteorological recordings suggested that humidification of intake air was more continuous. Humidifier fever in winter may have been the major influence on the formulation of the symptom pattern thought to be relevant for recognition of the disorder. A form of the illness, however, can occur during the summer which is camouflaged by intermittent humidification when the symptoms appear to be more closely associated with cool nocturnal air intake and unrelated to the pattern of attendance at work.